Relationship of physical activity and cognitive functioning among breast cancer survivors: a cross-sectional analysis - Hartman, Sheri J.; Zablocki, Rong W.; Tam, Rowena M.; Palmer, Barton W.; Parker, Barbara A.; Sears, Dorothy D.; Ahles, Tim A.; Natarajan, Loki (Frontiers in Cognition, 2024)
Cancer related cognitive decline is a common long-term side effect of cancer and its treatments among breast cancer survivors. Physical activity is a modifiable risk factor related to cognitive decline. However, existing research lacks consensus regarding the relationship between cognition and exercise as well as the impact of cancer treatments on this relationship. Baseline data from an ongoing randomized clinical trial was utilized to examine the relationship between self-reported and objectively measured cognition with physical activity. Exploratory analyses examined cancer treatments as potential moderators. Methods: Breast cancer survivors (N= 253) completed a battery of neurocognitive tests, the PROMIS Cognitive abilities questionnaire, medical charts abstracted for treatment information, and wore an ActiGraph accelerometer at the waist for 7 days. Data were analyzed using multiple linear regression models. Results: Participants were on average 58.5 (SD=8.88) years old, diagnosed 3 years prior to enrollment (SD=1.27) with 57% treated with chemotherapy and 80% receiving hormone therapy at baseline. Better self-reported cognitive ability was significantly associated with greater minutes of moderate to vigorous physical activity (MVPA; β= 0.070, se=0.028, p= 0.012). There were no significant associations with any objectively measured cognitive domains. Time since diagnosis was a significant moderator of MVPA and Processing Speed (β= -0.103, se=0.043, p= 0.017). Treatment with chemotherapy and/or hormones did not significantly moderate the relationship between MVPA and any of the cognitive measures or domains. Conclusion. Findings suggest that physical activity is related to self-reported cognition but not objectively measured cognition. Greater physical activity was associated with faster processing speed in participants closer in time to their cancer diagnosis. These results emphasize the need for more research to understand when cancer survivors may benefit from physical activity and what aspects of cognition may be improved.